Peran Mediasi Kesadaran Merek Terhadap Pengaruh Pemasaran Media Sosial Terhadap Keputusan Pembelian di Kopi Kenangan di Pekanbaru - Muhammad Nurfakhri; Taufiqurrahman Taufiqurrahman; Prima Andreas Siregar (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study analyzes the effect of social media marketing on purchase decisions with brand awareness as a mediating variable among Kopi Kenangan consumers in Pekanbaru. Using a quantitative approach with 100 respondents selected through purposive sampling, data were analyzed using validity and reliability tests, path analysis, and Necessary Condition Analysis (NCA). The results indicate that social media marketing has a positive and significant effect on both brand awareness and purchase decisions, brand awareness is proven to mediate the relationship between the two, and both variables are necessary conditions for increasing purchase decisions.